2014
DOI: 10.1002/cmdc.201300531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Tumor‐Vasculature‐Disrupting Agent Verubulin and Two Heteroaryl Analogues on Cancer Cells, Endothelial Cells, and Blood Vessels

Abstract: Two analogues of the discontinued tumor vascular-disrupting agent verubulin (Azixa®, MPC-6827, 1) featuring benzo-1,4-dioxan-6-yl (compound 5 a) and N-methylindol-5-yl (compound 10) residues instead of the para-anisyl group on the 4-(methylamino)-2-methylquinazoline pharmacophore, were prepared and found to exceed the antitumor efficacy of the lead compound. They were antiproliferative with single-digit nanomolar IC50 values against a panel of nine tumor cell lines, while not affecting nonmalignant fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 56 publications
1
31
0
1
Order By: Relevance
“…Disruption of small blood vessels, as well as hemorrhages as a result of leaking or broken vessels were observed shortly after administration of VDAs, e.g. verubulin [162], or the microtubule-depolymerizing agent C9 [163]. Moreover, the growth of solid tumors on the surface of the CAM was successfully inhibited by VDAs, e.g.…”
Section: Cam As a Screening Platformmentioning
confidence: 99%
“…Disruption of small blood vessels, as well as hemorrhages as a result of leaking or broken vessels were observed shortly after administration of VDAs, e.g. verubulin [162], or the microtubule-depolymerizing agent C9 [163]. Moreover, the growth of solid tumors on the surface of the CAM was successfully inhibited by VDAs, e.g.…”
Section: Cam As a Screening Platformmentioning
confidence: 99%
“…[20,24] Interestingly,i nt he isoCA-4 analogues 1-3,s ubstitution of the 3,4,5-trimethoxy-phenylAring with heterocyclic structures has received very little attention. [25][26][27] In 2007, Cai and colleagues [25,26] reported the discovery of MPC-6827, whichc ontainsaquinazolinen ucleus, as ap otent cytotoxic (GI 50 :6 n m towardH CT cellsa mong others) and apoptosis-inducing small molecule (EC 50 :2n m)t hat prevents microtubule formationw ith potencye qual to that of vinblastin. Given the structural similarities between MPC-6827 and azaisoerianin derivatives 3,w epreparedaseries of novel derivatives 4,a sisoCA-4a nalogues,i nw hich aq uinazoline ring replaces the "traditional" 3,4,5-trimethoxyphenyl unit.…”
Section: Introduction Combretastatinmentioning
confidence: 99%
“…Verubulin (MPC‐6827) ( 30 ) is a quinazoline derivative that showed potent antineoplastic activities against diverse tumors and promoted apoptosis in both sensitive and MDR cancer cell phenotypes . Other verubulin analogs have been developed in an attempt to maintain potency and avoid resistance, and these compounds have reported vascular disrupting activities and low IC 50 values against various cancer cells . Mahal et al reported an analog of verubulin bearing an indole moiety N ‐(methylindolyl)aminoquinazoline10 ( 37 ), which showed good vascular disrupting effects with low nanomolar IC 50 values ranging from 0.4 to 5.8 nM against several cell lines.…”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 99%
“…Other verubulin analogs have been developed in an attempt to maintain potency and avoid resistance, and these compounds have reported vascular disrupting activities and low IC 50 values against various cancer cells . Mahal et al reported an analog of verubulin bearing an indole moiety N ‐(methylindolyl)aminoquinazoline10 ( 37 ), which showed good vascular disrupting effects with low nanomolar IC 50 values ranging from 0.4 to 5.8 nM against several cell lines. Additionally, some other tetrahydroquinoline analogs of verubulin 1b ( 38 ) were designed and synthesized by Wang’s group .…”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 99%
See 1 more Smart Citation